2020
DOI: 10.1089/photob.2019.4713
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Evaluation of Gingival Ablation with Various Laser Systems and Electroscalpel

Abstract: Objective: The aim of this study was to perform a systematic and multifaceted comparison of thermal effects during soft tissue ablation with various lasers and an electroscalpel (ES). Materials and methods: Er:YAG, Er,Cr:YSGG, CO 2 , Diode, Nd:YAG lasers (1 W, pulsed or continuous wave), an ES, and a scalpel (Sc; control), were employed for porcine gingival tissue ablation. Temperature changes during ablation were measured by using an infrared thermal imaging camera and a thermocouple. After ablations, the wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…As the bibliography indicates, other minimally invasive techniques could be used in the management of the soft tissue, such as laser systems (Er:YAG or Er,Cr:YSGG), according to the expert’s skills, with similar results. [ 42 , 43 , 44 ]. Some publications suggest that complications can be higher in patients with HIV, and therefore the viral load (CD4/CD8 ratio) must be stable [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the bibliography indicates, other minimally invasive techniques could be used in the management of the soft tissue, such as laser systems (Er:YAG or Er,Cr:YSGG), according to the expert’s skills, with similar results. [ 42 , 43 , 44 ]. Some publications suggest that complications can be higher in patients with HIV, and therefore the viral load (CD4/CD8 ratio) must be stable [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Er:YAG laser is a surface-absorption laser, and the findings from our recent ex vivo study showed that it causes the least thermal damage to surrounding tissue compared with that of other lasers, including carbon dioxide, neodymium-doped yttrium aluminum garnet, diode, and Er,Cr:YSGG lasers, particularly when it used in combination with a water spray. 30 The minimal thermal effects of Er:YAG lasers are advantageous for inspecting lased surfaces, subsequent wound healing, and pain control. Thus, we consider Er:YAG lasers to be the most suitable for esthetic soft tissue management.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, soft-tissues surgical procedures such as frenectomy and mucocele removal with diode or Nd:YAG lasers could be performed within a few minutes, reducing the need for anesthesia or wound care and therefore reducing the fear of the patient [85] . Besides, diode laser has positively influenced the post-surgical wound healing by the acceleration of the epithelial regeneration, providing lower postoperative pain and discomfort than conventional techniques [86] , [87] , [88] .…”
Section: Biophotonics Approachesmentioning
confidence: 99%